Evaluation of Tumor Heterogeneity of Prostate Carcinoma by Flow- and Image DNA Cytometry and Histopathological Grading - Naining Wang; Claudia Wilkin; Alfred Böcking; Bernhard Tribukait (Analytical Cellular Pathology)
Background. Heterogeneity of prostate carcinoma is one of the reasons for pretreatment underestimation of tumor aggressiveness. We studied tumor heterogeneity and the probability of finding the highest tumor grade and DNA aneuploidy with relation to the number of biopsies. Material and methods. Specimens simulating core biopsies from five randomly selected tumor areas from each of 16 Böcking’s grade II and 23 grade III prostate carcinomas were analyzed for tumor grade and DNA ploidy by flow‐ and fluorescence image cytometry (FCM, FICM). Cell cycle composition was measured by FCM. Results. By determination of ploidy and cell cycle composition, morphologically defined tumors can further be subdivided. Heterogeneity of tumor grade and DNA ploidy (FCM) was 54% and 50%. Coexistence of diploid tumor cells in aneuploid specimens represents another form of tumor heterogeneity. The proportion of diploid tumor cells decreased significantly with tumor grade and with increase in the fraction of proliferating cell of the aneuploid tumor part. The probability of estimating the highest tumor grade or aneuploidy increased from 40% for one biopsy to 95% for 5 biopsies studied. By combining the tumor grade with DNA ploidy, the probability of detecting a highly aggressive tumor increased from 40% to 70% and 90% for one and two biopsies, respectively. Conclusion. Specimens of the size of core biopsies can be used for evaluation of DNA ploidy and cell cycle composition. Underestimation of aggressiveness of prostate carcinoma due to tumor heterogeneity is minimized by simultaneous study of the tumor grade and DNA ploidy more than by increasing the number of biopsies. The biological significance of coexistent diploid tumor cell in aneuploid lesions remains to be evaluated.